Oral health-related quality of life in elderly population of the geriatric centers in the municipality of Pedro Moncayo, Ecuador - Zurita-Herrera, José David; Farfán-Mera, Karina Patricia; Hermosa-Gallardo, Dayana Nicole; Oña-Toapanta, Ingrid Antonella; Niama-Bonifaz, Esteban Javier (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Introduction: the objective of this study was to assess the oral health-related quality of life (OHRQoL) in older adults attending the gerontological centers of Cantón Pedro Moncayo. Methods: a cross-sectional study was conducted with a convenience sample of 61 older adults from three Gerontological Centers located in the Pedro Moncayo Canton in Ecuador, who signed the informed consent form and met the inclusion criteria. Special assistance was provided to participants aged 87 to 100 years, during the survey by trained personnel. Data were collected through 2 sections: the first with data on age, sex, and prosthesis use, while the second section comprised the OHIP-Sp questionnaire consisting of 49 items with 7 sections. The SPSSv.26 statistical program was used to analyze the data. Results: significant differences in OHRQoL, as measured by OHIP-Sp, were observed across sociodemographic factors. Older adults aged 76 to 85 years, male sex and those without prosthesis had a higher mean score, respectively. Physical disability had the highest score (13.95 ± 3.90), indicating a poorer OHRQoL, while social disability had the lowest score (4.67 ± 2.83), associated with better OHRQoL. Conclusion: according to the results of the OHIP-Sp, it became evident that this group of older adults experienced deficiency in the OHRQoL, with the male sex being the most affected across different dimensions.